2017
DOI: 10.1016/j.vprsr.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of dioctophymosis in canines within a riparian zone of the Río de La Plata watercourse, in Ensenada, Buenos Aires Province, Argentina

Abstract: SummaryDioctophymosis is a parasitic disease occasioned by the so-called "giant kidney worm", Dioctophyme renale, a nematode with an indirect life cycle. This parasite's definitive host is the mink, Mustela vison, though numerous wild and domestic mammals as well 1 as man can serve as final hosts. The worms also can be in ectopic locations in the body.We surveyed 692 canines by ecography, urine sampling, surgery, necropsy, and clinical examination and diagnosed 244 cases of dioctophymosis (35.3%). Of the cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Brazil is the country with the highest number of reported D. renale cases in domestic dogs with prevalence rates up to 14.2% (Ferreira et al, 2010;Nakagawa et al, 2007;Pedrassani et al, 2017;Rappeti et al, 2017). Canine dioctophymatosis has also been reported recently in other Latin America countries, such as Colombia (Florez et al, 2018) and Argentina (Radman et al, 2017). Recent studies have also reported D. renale in dogs in Iran (Vafae Eslahi et al, 2017;Zolhavarieh et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Brazil is the country with the highest number of reported D. renale cases in domestic dogs with prevalence rates up to 14.2% (Ferreira et al, 2010;Nakagawa et al, 2007;Pedrassani et al, 2017;Rappeti et al, 2017). Canine dioctophymatosis has also been reported recently in other Latin America countries, such as Colombia (Florez et al, 2018) and Argentina (Radman et al, 2017). Recent studies have also reported D. renale in dogs in Iran (Vafae Eslahi et al, 2017;Zolhavarieh et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Inside the definitive host, the Dioctophyma larva penetrates the intestinal or duodenal mucosa, enters the peritoneal cavity and migrates to the kidney, where it develops and matures into the adult form (Bowman, 2014;Pedrassani et al, 2017). Adults are able to live up to 3 years in the definitive host and the fertilized eggs that are shed into the environment may survive for up to 5 years (Radman et al, 2017). D. renale nematodes are most commonly found inside the renal pelvis where they mature, however they can also be encysted within the abdominal cavity, the uterus, ovary, mammary gland, urethra, subcutaneous tissues of the inguinal region and in the mesenteric lymph nodes (Bowman, 2014;Nakagawa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this study showed that the ultrasound negative animal, whose parasite was migrating, tested positive in the ELISA, demonstrating that this technique can establish an early diagnosis before the parasite is located in the kidney and, consequently, decrease the aggravations caused by dioctophimosis. Thus, early diagnosis helps maintain the kidney parenchyma preserved, therefore not requiring the patient to undergo nephrectomy, maintaining the patient’s kidney preserved and resulting in higher quality and life expectancy ( Radman et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fishing is especially dangerous for those who may practice it and not properly cook the fish before consumption. This risk extends to domestic animals that accompany these fishermen who may offer raw fish and/or offal to them ( Radman et al, 2017 ; Russo et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%